Terapi Realitas untuk Meningkatkan Penerimaan Ibu yang Memiliki Anak Berkebutuhan Khusus di Kabupaten Nganjuk - Wahyu Utami; Sun Fatayati (Universitas Islam Tribakti Lirboyo Kediri, 2021)
It is estimated that 20% of children with special needs are from mothers who are over 35 yearsold. In some cases, people tend to stay away from individuals with special needs, not infrequently, they are also humiliated and even isolated. Worse, this rejection is not only done by the general public, but also by families and families. Sample subjects in this study were housewives with an age range of 35-41 years. The sampling technique used purposive sampling with the criteriaof parents who have children with special needs on a low scale in the acceptance of children with special needs. The researchmethod uses observation, interviews and children's measurement scales. The intervention given to reality therapy subjects was 9 sessions. The results of the intervention showed that the t-test pair obtai ned the t-test value of 11,731 with a significance value of 0.000 (p <0.05) so that the existing data had the effect of treatment on the test data. This shows that parents have an increased level ofacceptance of children with special needs through the provision of reality therapy. Thismeans that this research shows a decrease in the response rate of mothers to children.